Surgical Treatment of Skin Ulcers in Patients with Werner’s Syndrome: A Literature Overview - Radavičiūtė, Viltė (Lietuvos chirurgija, 2024)
Introduction. Werner’s syndrome is a rare autosomal recessive disorder characterised by premature ageing phenotypes, including skin ulcers resistant to conservative treatment. Purpose. To review the cases of surgical treatment of skin ulcers in patients with Werner’s syndrome published in the scientific literature. Methods. Scientific articles were searched using Google Scholar, PubMed and DeepDyve databases, applying the keyword “ulcer” and the word combination “Werner’s syndrome”. Based on the inclusion and exclusion criteria, 16 scientific publications were included in the review. Results. Depending on the location and nature of the ulcers in patients with Werner’s syndrome, different surgical options are available, with different surgical outcomes, such as partial or complete ulcer healing, non-healing or recurrence. Conclusions. In skin grafting, ulcers are more likely to heal incompletely or temporarily. Therefore additional treatment options can be used such as vacuum negative pressure therapy, Kirschner wires or removal of the upper layer of bone. Other grafts, such as artificial skin, are more reliable, especially in large joint areas. However, a critical assessment of each individual case is necessary before choosing surgical treatment, as these patients have different degrees of tissue blood flow, muscle atrophy and general condition.
Keywords: Werner's syndrome; ulcer; surgery